Multiparametric Analyses of Hepatocellular Carcinoma Somatic Mouse Models and Their Associated Tumor Microenvironment. Issue 6 (8th June 2021) - Taranto, Daniel; Ramirez, Christel F.A.; Vegna, Serena; de Groot, Marnix H.P.; de Wit, Niels; Van Baalen, Martijn; Klarenbeek, Sjoerd; Akkari, Leila
Abstract: The rising incidence and increasing mortality of hepatocellular carcinoma (HCC), combined with its high tumor heterogeneity, lack of druggable targets, and tendency to develop resistance to chemotherapeutics, make the development of better models for this cancer an urgent challenge. To better mimic the high diversity within the HCC genetic landscape, versatile somatic murine models have recently been developed using the hydrodynamic tail vein injection (HDTVi) system. These represent novel in vivo tools to interrogate HCC phenotype and response to therapy, and importantly, allow further analyses of the associated tumor microenvironment (TME) shaped by distinct genetic backgrounds. Here, we describe several optimized protocols to generate, collect, and experimentally utilize various samples obtained from HCC somatic mouse models generated by HDTVi. More specifically, we focus on techniques relevant to ex vivo analyses of the complex liver TME using multiparameter flow cytometric analyses of over 21 markers, immunohistochemistry, immunofluorescence, and histochemistry. We describe the transcriptional assessment of whole tissue, or of isolated immune subsets by flow‐cytometry‐based cell sorting, and other protein‐oriented analyses. Together, these streamlined protocols allow the optimal use of each HCC murine model of interest and will assist researchers in deciphering the relations between cancer cell genetics and systemic and local changes in immune cell landscapes in the context of HCC progression. © 2021 The Authors. Current Protocols published by Wiley Periodicals LLC. Basic Protocol 1 : Generation of HCC mouse models by hydrodynamic tail vein injection Basic Protocol 2 : Assessment of HCC tumor progression by magnetic resonance imaging Basic Protocol 3 : Mouse sacrifice and sample collection in HCC mouse models Support Protocol 1 : Preparation of serum or plasma from blood Basic Protocol 4 : Single‐cell preparation and HCC immune landscape phenotyping by flow cytometry Alternate Protocol 1 : Flow cytometric analysis of circulating immune cells Support Protocol 2 : Generation, maintenance, and characterization of HCC cell lines Support Protocol 3 : Fluorescence‐activated cell sorting of liver single‐cell preparation Basic Protocol 5 : Preparation and immunohistochemical analysis of tumor tissues from HCC‐bearing liver Alternate Protocol 2 : Preparation and analyses for immunofluorescence staining of HCC‐bearing liver Support Protocol 4 : Liver‐specific phenotypic analyses of liver sections Support Protocol 5 : Immunohistochemical quantification in liver sections Basic Protocol 6 : Preparation of snap‐frozen tumor tissue from extracted liver and transcriptional analyses of bulk tumor or sorted cells Alternate Protocol 3 : Protein analyses from HCC samples and serum or plasma